On Mahler—Sprindzuk’s theorem - Sliesoraitienė, R. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Р. Слесорайтене. О теореме Малера—Спринджука R. Sliesoraitienė. Apie Malerio—Sprindžiuko teoremą